2014
DOI: 10.1177/2325957414554005
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Nasal Carriage of Staphylococcus aureus in HIV-Infected Individuals in Comparison to HIV-Uninfected Individuals: A Case–Control Study

Abstract: The study was conducted to evaluate the prevalence of nasal colonization of Staphylococcus aureus in individuals with HIV infection attending the Integrated Counselling and Testing Centre in a teaching hospital and compare the prevalence with HIV-uninfected individuals. A case-control study was conducted among newly diagnosed HIV-infected individuals and an equal number of age-group and sex-matched HIV-uninfected individuals, and nasal swabs were collected from both the samples. Sociodemographic and clinical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 13 publications
1
21
1
Order By: Relevance
“…More recent studies have shown nasal colonization rates of 20 % to 30 % (Andersen et al 2012;Gamblin et al 2013;Mernelius et al 2013b;Olsen et al 2013;Mehraj et al 2014). Nasal colonization rates of up to nearly 60 % have been reported among HIV-positive patients (Kotpal et al 2014), patients on hemodialysis (Duran et al 2006), intravenous drug addicts and patients with insulin dependent diabetes (Kluytmans et al 1997). Several studies have shown that carriage and colonization in the throat is more common than colonization of the anterior nares (Nilsson & Ripa 2006;Hamdan-Partida et al 2010;Mernelius et al 2013b).…”
Section: Carriage and Colonizationmentioning
confidence: 99%
“…More recent studies have shown nasal colonization rates of 20 % to 30 % (Andersen et al 2012;Gamblin et al 2013;Mernelius et al 2013b;Olsen et al 2013;Mehraj et al 2014). Nasal colonization rates of up to nearly 60 % have been reported among HIV-positive patients (Kotpal et al 2014), patients on hemodialysis (Duran et al 2006), intravenous drug addicts and patients with insulin dependent diabetes (Kluytmans et al 1997). Several studies have shown that carriage and colonization in the throat is more common than colonization of the anterior nares (Nilsson & Ripa 2006;Hamdan-Partida et al 2010;Mernelius et al 2013b).…”
Section: Carriage and Colonizationmentioning
confidence: 99%
“…14 Various studies have been proved that HIV is a risk factor for colonization of S. aureus and MRSA. 3,15,16 In this study, among the newly diagnosed HIV positive population, S. aureus nasal carriage was found around 43.64 % in which 18.75% were MRSA whereas the carriage rate was 21.82 % and 6.25% for S. aureus and MRSA in control group. This finding approves HIV as a risk factor for nasal colonization.…”
Section: Discussionmentioning
confidence: 51%
“…In an Indian case-control study, the prevalence of S aureus colonization in HIV-infected individuals was nearly 4 times that of non-HIV individuals (44% vs 12%). 94 Although S aureus colonization is common, the prevalence of MRSA colonization among the S aureus isolates is variable. The study by Giuliani and colleagues 93 showed that although 23.1% of their HIV-infected men who have sex with men cohort was colonized with S aureus, none of them were colonized with MRSA.…”
Section: Incidence and Risks For Methicillin-resistant Staphylococcusmentioning
confidence: 99%
“…The study by Giuliani and colleagues 93 showed that although 23.1% of their HIV-infected men who have sex with men cohort was colonized with S aureus, none of them were colonized with MRSA. Other studies that showed relatively low prevalence of MRSA colonization included the study by Kotpal and colleagues 94 in which only 6% of subjects were colonized, and the study by Crum-Cianflone and coworkers, 92 in which only 4% of subjects were colonized. Other studies showed higher rates of MRSA colonization in HIV-infected individuals of 11% from Popovich and colleagues, 89 13.3% from Chacko and colleagues, 91 15.4% from Farley and colleagues, 95 and 13% to 15% between baseline and 12 months.…”
Section: Incidence and Risks For Methicillin-resistant Staphylococcusmentioning
confidence: 99%